THE EFFECTIVENESS OF MONETARY POLICY IN THE EURASIAN ECONOMIC UNION - GOLODOVA, Zhanna; SHKVARYA, Lyudmila; BONDARCHUK, Natalia; KOLOSOVA, Ekaterina (CENTRAL ASIA AND THE CAUCASUS, 2017)
Whereas the establishment of all previous alliances in the post-Soviet space was motivated by a desire for political union, the Eurasian Economic Union (EAEU) has focused on the economic component. One of its goals has been defined as a transition to a coordinated and concerted economic policy, including fiscal and monetary policies. Some decisions in this area are already being taken. But in light of the global financial and economic crisis, central banks have had to pursue a looser monetary policy, while governments in all EAEU countries have increased their influence on central bank decisions. There are differences in this respect: in some countries (Belarus and Russia), the primary objective of the central bank has not been identified at all and there is a multiplicity of objectives; in others, one and the same objective—the achievement of price stability—is defined as both the objective of the monetary authority and the goal of its monetary policy. In Belarus and Russia, price stability is regarded as a means of ensuring the stability of the national currency (the ruble). In order to coordinate the key elements of monetary policy across the EAEU, the authors suggest setting a primary objective for the central bank, vesting it with exclusive authority in the area of monetary policy, and increasing its real independence.